ZrO2 Coatings on Ti-6Al-4V Alloy by Using R. F. Plasma - Raheem Lafta Ali (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Titanium alloy (Ti-6Al-4V) has been used in biomedical applications due to its biocompatibility and mechanical properties. However, it has a possible toxic effect resulting from released vanadium and aluminum. The Zirconium Oxide ZrO2 coated Ti-6Al-4V alloy prevented releasing of undesirable vanadium and aluminum. The aim of this paper is to investigate the structural and mechanical properties of Ti-6Al-4V alloy by coating with ZrO2. This coating was prepared by Radio Frequency Sputtering (RF) method. The thin film of ZrO2 was improved the structural, composition were characterized by X-ray diffraction (XRD), Field Emission- Scan Electron Microscope (FE-SEM).The ZrO2 films were crystalline structure.
Keywords: Titanium alloy; Zirconium Oxide; R. F. plasma